An unusual presentation of primary splenic hydatid cyst - Kar, Jugal K (Medknow Publications & Media Pvt Ltd, 2011)
The larval form of the parasite Echinococcus granulosus causes a hydatid cyst. The most common sites are liver and lungs. We present an unusual case of an isolated primary hydatid cyst of the spleen. In our case, ultrasonography images of the spleen were not suggestive of hydatid disease except a large cystic lesion. We proceeded to conservative splenectomy that detected hydatid cyst incidentally during operation. This issue is considered common in our geographical area. A high suspicion of this disease is justified in endemic regions. Moreover, medical treatment should precede and follow the surgical intervention.